Effects of perceived racial discrimination on appetite and eating behaviour - Farah Sabrina Abdul Rashid (2019)
Ethnic minorities in developed countries tend to experience higher levels of obesity and diabetes. They are also the targets of discrimination by ethnic majority groups. Literature has shown that perceived discrimination can negatively impact one’s psychological and physical health. Past research has also shown that a decrease in subjective socioeconomic status resulted in participants consuming larger portion sizes. We believe that the feeling of one’s resources and socioeconomic attainment being threatened in the form of racial discrimination will bring about the same outcome. Prior to this, no other studies to our knowledge had investigated the relationship between perceived discrimination and appetite. We hypothesized that experiencing perceived discrimination will result in one selecting larger portion sizes. We manipulated participants perceived racial discrimination through a newspaper task and measured their appetite with the use of a portion selection task. Although no significant relationship was found between the two variables of interest, we found a significant correlation between subjective socioeconomic status and appetite in the discrimination condition. We also found a moderation effect of condition on subjective socioeconomic status and high energy-dense foods. There is potential for a similar study to be done on a socioeconomically disadvantaged sample and on different forms of eating behavior with regards to racial discrimination.